The The Development of a Training Curriculum for Southern Folk Performance ‘Nora’ to Enhance the Competencies of Dance Instructors: ไม่มี - BUATHONG, KANARAT; Srisopa, Jaruwat; tumphet, Rattanachai; Cherdchoo, Nittaya; Sithsungnoen, Chanasith; Suwanampha , Tanakorn (Mahachula Academic Journal, 2026)
This research aimed to ๑) investigate fundamental information and needs for curriculum development, and ๒) develop and examine the quality of a training curriculum on Southern Thai folk performance “Nora” to enhance the competencies of dance teachers. The study employed a Research and Development (R&D) approach and mixed-method data collection. The target group for the needs assessment consisted of ๓๘ participants, and ๗ experts were involved in curriculum evaluation. Research instruments included document analysis forms, interview forms, needs assessment surveys, focus group discussion protocols, and curriculum suitability evaluation forms. Quantitative data were analyzed using mean and standard deviation, while qualitative data were analyzed through content analysis. The findings revealed that: ๑) dance teachers who did not graduate in the field of dance expressed the highest level of need for developing practical skills in the ๑๒ standard Nora dance postures, Nora costume dressing, and practice-based instructional management Percentile ๓๒.๑๒ %; ๒) the developed curriculum comprised ๑๐ components: principles, objectives, structure, learning experiences/content, instructional approaches, instructional media/resources, measurement and evaluation, instructor qualifications, participant qualifications, and lesson plans; ๓) the Index of Item-Objective Congruence (IOC) ranged from ๐.๘๐ – ๑.๐๐ ; and ๔) the overall curriculum suitability was rated at the High level (M = ๔.๔๔, SD = ๐.๘๗)